"Violence and love and drugs…it all goes hand in hand": A mixed methods analysis of the substance abuse, violence, and HIV/AIDS syndemic among women who use methamphetamine. Issue 4 (2nd October 2021) - Stockman, Jamila K.; Syvertsen, Jennifer L.; Hayashi, Hitomi D.; Ludwig-Barron, Natasha; Tsuyuki, Kiyomi; Morris, Meghan D.; Palinkas, Lawrence A.
Abstract: Background: The synergistic epidemics of substance use, violence, and HIV/AIDS, also known as the SAVA syndemic, disproportionately affects vulnerable women in the United States. Methamphetamine use is closely linked with physical and sexual violence, including intimate partner violence (IPV), which heightens women's vulnerability to HIV. This mixed methods study examined the prevalence and correlates of violence among women who use methamphetamine, ( n = 209) enrolled in an HIV intervention study in San Diego, California. Methods: At baseline, 209 women completed an interviewer-administered computer-assisted survey. A sub set of women who reported lifetime IPV ( n = 18) also participated in qualitative interviews to contextualize our understanding of patterns of violence over time. Results: In the overall cohort, reports of lifetime (66.0%) and past 2-month (19.6%) IPV were prevalent. Moreover, women reported lifetime physical only (27.3%), sexual only (6.2%), or both forms of violence (50.7%) by multiple perpetrators. Factors independently associated with lifetime IPV were having unprotected sex with a steady partner (odds ratio [OR]: 2.50, 95% confidence interval [CI]: 1.04, 6.00) and being high on methamphetamine during unprotected sex with a steady partner (OR: 2.56, 95% CI: 1.30, 5.09) within the past 2 months. Our qualitative narratives illuminated how IPV in women's steady relationships often reflects a culmination of violent victimization throughout their lifetime which is further exacerbated by methamphetamine use and sexual risk through gendered power dynamics. Conclusions: HIV prevention interventions should address the SAVA syndemic in a holistic manner, including the role of methamphetamine use in the context of women's abusive steady relationships.